2005
DOI: 10.1111/j.1600-6143.2005.01057.x
|View full text |Cite
|
Sign up to set email alerts
|

Kidney Transplant in Black Recipients: Are African Europeans Different from African Americans?

Abstract: Demographic characteristics were similar for the two cohorts other than cause of end-stage renal failure (more hypertension among AE and more polycystic kidney disease among Cauc) and cold ischemia time (significantly longer for AE). Immunosuppressive treatment was comparable between groups. There were no significant differences between AE and Cauc in the incidence of acute rejection (31% vs. 30%). At 5 years post-transplant, patient survival (93% vs. 92%), graft survival (83% in both groups) and graft functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
42
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(49 citation statements)
references
References 32 publications
6
42
1
Order By: Relevance
“…These data suggest that dialysis-related environmental stimuli, rather than inherent variability of the T cell response, may contribute to immunologic differences between ethnic groups. One recent analysis of black European kidney transplant recipients found no increased rate of rejection compared with a white cohort (17). The black European patients who were analyzed seemed to have greater resources than many black transplant candidates (18), and dialysis vintage was not different between ethnic groups in this study (E. Thervet, Hospital Necker, Paris, France; personal communication, April 10, 2006).…”
Section: Discussionmentioning
confidence: 83%
“…These data suggest that dialysis-related environmental stimuli, rather than inherent variability of the T cell response, may contribute to immunologic differences between ethnic groups. One recent analysis of black European kidney transplant recipients found no increased rate of rejection compared with a white cohort (17). The black European patients who were analyzed seemed to have greater resources than many black transplant candidates (18), and dialysis vintage was not different between ethnic groups in this study (E. Thervet, Hospital Necker, Paris, France; personal communication, April 10, 2006).…”
Section: Discussionmentioning
confidence: 83%
“…A recent study from France showed comparable renal transplant outcomes for both white patients and patients of African descent. 36 Although less comparable to Canada, Brazil has also been shown to have similar graft survival among black versus white patients in the recipients of living-donor kidneys. 37 There are a number of limitations to our study.…”
Section: Discussionmentioning
confidence: 99%
“…In France, which also has universal health coverage, Black recipients do as well as Caucasians [7]. The authors postulated that if significant physiologic differences between Blacks and Whites existed, they should be evidence worldwide, not limited to a single country such as the USA.…”
Section: Introductionmentioning
confidence: 99%